Evaluating the cost-effectiveness of universal hepatitis B virus vaccination in Iran: a Markov model analysis - Ali Mohammad Mokhtari; Mohsen Barouni; Mohsen Moghadami; Jafar Hassanzadeh; Rebecca Susan Dewey; Alireza Mirahmadizadeh (Taylor & Francis Group, 2021)
Vaccination is an essential way to prevent the transmission of hepatitis B virus (HBV). Various studies have been published on the cost-effectiveness of HBV vaccination, but since the results vary according to the target population and related health outcomes, this study examined the cost-effectiveness of the universal HBV vaccination in Iran. In this economic evaluation study, a decision tree with the Markov model was used to compare the universal HBV vaccination with a strategy of non-vaccination. Health states used in the model included healthy, chronic hepatitis B, compensated cirrhosis, decompensated cirrhosis, hepatocellular carcinoma, and death. Analyses were performed from a payer's perspective. Incremental cost-effectiveness ratio (ICER) per life-year gained, and quality-adjusted life-years (QALYs) gained were calculated at a 5% annual discount rate. The sensitivity analysis was conducted using Monte Carlo simulation. Analyses were performed using Microsoft Excel and TreeAge Pro 2011 software. In 2017, the estimated cost per dose for any HBV vaccine was $3.20 USD. The universal HBV vaccination was economically advantageous compared to non-vaccination, and the estimated cost of this program per life-year and QALY gained were $6,319 and negative (-) $1,183.85 USD, respectively. Given the uncertainty of all parameters, the model remained robust and reliable. In Iran, the universal HBV vaccination strategy for both health outcomes of QALY and life-years gained was cost-effective and advantageous. The vaccination strategy saved money, increased life years and improved quality of life. Therefore, it is recommended that this program continues to be provided.